Posters relating to Aboriginal & Torres Strait Islander Employment. - Aboriginal & Torres Strait Islander Employment Network ([Queensland] : ATSIE, 1990)
Posters featuring artworks by the following Indigenous artists: Joanne Currie Nalingu, Pricilla Seden, Sophie Buli and Ethel (Moonie) Doctor.
1. Coast to Desert by artist: Joanne Currie Nalingu, depicts the journey to the Rainbow Serpent across the land -- 2. Blue Shark by artist: Pricilla Seden -- 3. [Illustration of coral garden with fishes, shells, turtles, dugongs and seaweeds] by artist: Sophie Buli -- 4. [Illustration of a snake] by artist: Ethel (Moonie) Doctor (nee: Georgetown)
Title devised by cataloguer.
Cultural sensitivity advisory notice: Aboriginal, Torres Strait Islander and other First Nations people are advised that this item may contain names, recordings, images of deceased people and other content that may be culturally sensitive.
"Department of Employment, Vocational Education, Training and Industrial Relations"--At foot of posters.
"This strategy is a joint inituative of both the Queensland and Commonwealth Governments"--At foot of posters.
Keywords: Nalingu, Joanne Currie; Seden, Pricilla; Buli, Sophie; Doctor, Ethel, -- 1930-1991; Artists, Aboriginal Australian -- Posters; Torres Strait Islanders -- Employment -- Australia -- Posters; Aboriginal Australians -- Employment -- Australia -- Posters; Education - Vocational and trades; Art - Artists - Women; Art - Artists - Education / training; Posters, Australian; Australia -- Posters; Australian